2022
DOI: 10.5423/ppj.nt.04.2022.0051
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Ice Nucleation Active Fusarium Strains from Rapid Apple Declined Trees in Korea

Abstract: In biological particles such as Fusarium species, ice nucleation activity (INA) has been observed. Fusarium strains isolated from apple declined trees in Korea were identified with a multilocus sequence analysis using the tef1 and rpb1 genes. Droplet-freezing and tube-freezing assays were used to determine the INA of the strains, using Pseudomonas syringae pv. syringae KACC 21200 as a positive control and resulting in seven INA+ fungal strains that were identified as F. tricinctum (KNUF- 21-F17, KNUF-21-F18, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Recently, Fusarium tricinctum has been reported as the causal agent of apple decline in China ( Zhang et al, 2022 ). In addition, studies have shown that the ice nucleation-active F. tricinctum and Fusarium diversisporum isolated from declined apple trees in Korea may be linked to RAD ( Avalos-Ruiz et al, 2022a , 2022b ). Thus, further research is needed for a comprehensive understanding of RAD as well as the identification of causal agents, which will contribute to combating this disease worldwide.…”
Section: Biotic Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Fusarium tricinctum has been reported as the causal agent of apple decline in China ( Zhang et al, 2022 ). In addition, studies have shown that the ice nucleation-active F. tricinctum and Fusarium diversisporum isolated from declined apple trees in Korea may be linked to RAD ( Avalos-Ruiz et al, 2022a , 2022b ). Thus, further research is needed for a comprehensive understanding of RAD as well as the identification of causal agents, which will contribute to combating this disease worldwide.…”
Section: Biotic Factorsmentioning
confidence: 99%
“…In Korea, PSS WSP007 was isolated from apple stem canker, and draft genomic analysis shed light on its life cycle, revealing that it exhibited INA ( Lee et al, 2023 ; Lim et al, 2019b ). At the same time, Fusarium strains obtained from declining apple trees in Korea have also been reported to show INA ( Avalos-Ruiz et al, 2022a , 2022b ). However, our understanding of the specific effects of INA caused by PSS or Fusarium species on different apple rootstocks depending on climatic conditions and geographic regions is still limited.…”
Section: Factors Linked To Rad: Cold Stress Accelerated By Ice Nuclea...mentioning
confidence: 99%
See 2 more Smart Citations